European AIDS Clinical Society Second Standard of Care Meeting, Brussels 16‐17 November 2016: a summary. Issue 2 (27th October 2017) - De Wit, S; Battegay, M; D'Arminio Monforte, A; Lundgren, JD; Oprea, C; Antinori, A; Bhagani, S; Fätkenheuer, G; Friis‐Moller, N; Furrer, H; Mussini, C; ,
Abstract : The European AIDS Clinical Society (EACS) organized a second meeting on Standard of Care in Europe on November 16‐17 th, 2016. The aims of the meeting were to discuss and propose actions on three topics, namely: Adherence to guidelines for treatment initiation, treatment monitoring and outcomes, Retention in care and HIV and tuberculosis co‐infection. Several actions need to be implemented in order to further improve quality of care and treatment of HIV in Europe. A common ground for standard of care, based on the EACS Guidelines should be established throughout Europe. EACS plans to interact with policy makers and other stakeholders to insure this common minimal level of standard of care, in particular for initiating of ART, accessibility of drugs and monitoring of ART with viral load. Progress should be made to monitor retention in care, prevent lost to follow and insure return to care. Improving integration of services and accessibility to care play a major role. Integration is also key for optimizing care of HIV‐tuberculosis co‐infection, as well as diagnosis and prevention of tuberculosis in population at risk. The Standard of Care meeting organized every other year by EACS provides a unique opportunity to monitor progresses and pitfalls in HIV patient care throughout Europe. It is also a forum for advocacy towards policy makers and other stakeholders to constantly improve HIV patient global management, aiming to provide the same level of quality on the whole continent.